Shared Attention at the Origin: On the Psychological Power of Descriptive Norms. (November 2015) - Shteynberg, Garriy
What is at the origin of a descriptive norm's power to influence people? The standard explanation posits that a perceived widespread frequency of a given behavior signals a groupwide attitudinal agreement with that behavior, which in turn further encourages that behavior. Alternatively, I argue that the psychological power behind descriptive norms lies in the social nature of the attentional mode in which typical behavior is encountered. I introduce the reader to recent research on shared attention and its cognitive, attitudinal, affective, and behavioral consequences. Then, I use the shared attention perspective to further understand the psychological power of descriptive norms.